2022
DOI: 10.15212/zoonoses-2022-0028
|View full text |Cite
|
Sign up to set email alerts
|

Host Immune Responses to Arthritogenic Alphavirus Infection, with Emphasis on Type I IFN Responses

Abstract: Arthritogenic alphaviruses, such as Ross River virus, chikungunya virus and O’nyong-nyong virus, cause endemic disease globally and are a major public health concern. The hallmarks of arthritogenic alphavirus disease are debilitating pain, and potentially chronic inflammation of the muscles, thus influencing quality of life. The type I IFN response is a major component of the innate immune response against arthritogenic alphaviruses, and is essential in inhibiting viral replication and dissemination. Type I IF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 139 publications
(165 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, Hallen et al ( 41 ) showed that Ifi44-high expression was associated with more neutrophils, NK cells, M1 macrophages, M2 macrophages, Th1 and Th2 CD4 + T cells, CD8 + effector memory T cells, and plasmacytoid dendritic cells in the tumor microenvironment. The higher level of Ifi44 gene in RRV-infected MXRA8 −/− mice might be a novel mechanism by which RRV modulates IFN response to facilitate replication in the absence of the entry receptor ( 44 , 45 ). The role of Cdkn1a and Ifi44 in alphavirus disease warrants further study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Hallen et al ( 41 ) showed that Ifi44-high expression was associated with more neutrophils, NK cells, M1 macrophages, M2 macrophages, Th1 and Th2 CD4 + T cells, CD8 + effector memory T cells, and plasmacytoid dendritic cells in the tumor microenvironment. The higher level of Ifi44 gene in RRV-infected MXRA8 −/− mice might be a novel mechanism by which RRV modulates IFN response to facilitate replication in the absence of the entry receptor ( 44 , 45 ). The role of Cdkn1a and Ifi44 in alphavirus disease warrants further study.…”
Section: Discussionmentioning
confidence: 99%
“…Viral RNA (single-stranded) can be detected by the cytosolic retinoic acid-inducible gene I (RIG-I)-like receptors (RLRs) to promote the expression of various host anti-alphaviral defenses, including the essential type-I interferons (IFNs). Hence, the downstream signals from the PRRs involve the activation of interferon regulatory factors (IRFs), leading to the production of IFNs and, subsequently, the signal transducer and activator of transcription (STAT)-dependent production of interferon-stimulated genes (ISGs) [ 18 ]. The immune response is achieved by a range of inflammatory mediators for the recruitment of other defensive cells and/or the infiltration of immune cells that may cause severe inflammation.…”
Section: Introductionmentioning
confidence: 99%